A Comparative Study Of Initial Stage Climate Responsive Design Guideline In Residential Settings Based On The Thermal Comfort Models Of Climate Consultant For Five Regions Of Pakistan - Khalid, Asma (European Journal of Sustainable Development, 2018)
Thermal comfort can be achieved by analyzing the dynamic behavior of the climate and considering all the architectural possibilities, as defined by the Climate Consultant for all five climate zones of Pakistan. The Climate Consultant software, lists 20 design guidelines (DGs) based on the design strategies and the criteria defined for each model. The comparative analysis of these guidelines helps to outline commonalities and differences in four Human Thermal Comfort models (HTCMs). The variety of guidelines achieved from these four thermal comfort models give the best possible combination of design guidelines for all five regions of Pakistan. The ASHRAE adaptive comfort model proposes a totally different set of guidelines, most suitable for naturally ventilated residential buildings. The California code, ASHRAE 55, and ASHRAE 2005 proposes a set of design guidelines with the largest possible similarity, suitable for all building types. The paper concludes similar climate responsive passive design principles using climate consultant software for the five climate regions of Pakistan. Keywords: Climate Consultant, Climate responsive buildings, Design guidelines, Human thermal comfort model, Passive design